1972
DOI: 10.1085/jgp.59.6.659
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Sodium Current in Myxicola Giant Axons

Abstract: Experiments were conducted on Myxicola giant axons to determine if the sodium activation and inactivation processes are coupled or independent. The main experimental approach was to examine the effects of changing test pulses on steady-state inactivation curves. Arguments were presented to show that in the presence of a residual uncompensated series resistance the interpretation of the results depends critically on the manner of conducting the experiment. Analytical and numerical calculations were presented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
106
1

Year Published

1974
1974
1997
1997

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 13 publications
(16 reference statements)
9
106
1
Order By: Relevance
“…Hence addition of 6 nM-TTX to the solution would reduce the currents to extremely low levels. Voltage drops across the membrane series resistance can produce a displacement of the h. (E) curve along the voltage axis (Goldman & Schauf, 1972). However, the shift is smaller than 1 mV for our pulse programmes, measured peak sodium currents and calculated series resistances.…”
Section: Discussionmentioning
confidence: 71%
“…Hence addition of 6 nM-TTX to the solution would reduce the currents to extremely low levels. Voltage drops across the membrane series resistance can produce a displacement of the h. (E) curve along the voltage axis (Goldman & Schauf, 1972). However, the shift is smaller than 1 mV for our pulse programmes, measured peak sodium currents and calculated series resistances.…”
Section: Discussionmentioning
confidence: 71%
“…This was confirmed by Chandler,Hodgkin & Meves (I965) on perfused squid axons. However, a sigmoid time course with a pronounced initial delay was found by Goldman & Schauf (1972) on Myxicola axons and by Bezanilla & Armstrong (1977) on perfused squid axons. The question whether the time course of inactivation is exponential or sigmoid is related to the question whether activation and inactivation are independent or coupled processes (see Meves, 1978, for review).…”
Section: Introductionmentioning
confidence: 79%
“…By contrast, Bezanilla & Armstrong (1977) and Goldman & Schauf (1972) had concluded that inactivation follows a sigmoid time course with a pronounced initial delay. Bezanilla & Armstrong used a conditioning pulse immediately followed by a test pulse.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A delay in the onset of inactivation has also been claimed for Myxicola axons (Goldman & Schauf, 1972;Schauf & Davis, 1975), for myelinated frog fibres (Peganov, 1973), and for frog skeletal muscle fibres (Campbell & Hille, 1976). In contrast, Chandler, Hodgkin & Meves (1965), Gillespie & Meves (1980) and Dodge (1963), performing two-pulse experiments on perfused squid giant axons and on nodes of Ranvier, respectively, did not detect a delayed onset of inactivation.…”
Section: Introductionmentioning
confidence: 88%